Telepractice application for the overt stuttering assessment of children aged 6–15 years old. Issue 5 (15th June 2022) - Aldukair, Lamya; Ward, David
Abstract: Background: Despite the importance of delivering speech and language therapy services to children who stutter (CWS), there are barriers to accessing speech and language therapy. One way to improve access for those who may otherwise be deprived of speech and language therapy services, including CWS, is through telepractice (TP). However, there is currently no evidence as to the viability of TP stuttering assessments for CWS. Aim: To investigate the validity and reliability, and acceptability of using a TP application to assess overt stuttering behaviour children aged 6–15 years. Methods & Procedure: A total of 30 CWS, aged between 6 and 15 years, were recruited from a speech therapy clinic in King Abdulaziz University Hospital in Riyadh, Saudi Arabia. Children were divided into two testing conditions, either face‐to‐face (f2f)‐led or TP‐led testing, and the Stuttering Severity Instrument (SSI‐IV) was administered, percentage of syllables stuttered (%SS) was calculated, and severity ratings (SR) assigned, either via f2f or via TP using two laptops with webcams, video conference software and a broadband internet connection. Agreement and reliability of scoring in the two testing conditions were reported in addition to findings from questionnaires exploring children's and their caregivers' perceptions both before and immediately after the TP assessment was carried out. Outcome & Results: A total of 30 sessions were successfully carried out, with results revealing unsatisfactory levels of agreement when applying the Bland and Altman method. However, when discrepancies were found, these were comparable with those from traditional f2f studies. Generally, parents and children exhibited high levels of satisfaction and held a positive view regarding TP pre‐ and post‐assessment. Conclusions & Implications: The results of the study suggest that conducting an overt stuttering assessment via TP for 6–15‐year‐olds CWS is reliable and valid. Although the TP model posed some (mainly technical) challenges for executing the assessment, high levels of satisfaction were recorded by parents and children alike. The TP system and equipment chosen in this study has provided a basis for the delivery of TP overt stuttering assessment in a clinical setting, thus addressing the barriers to access that are present for CWS. These results are preliminary, but they can be seen as a building block for future research in TP assessment studies for CWS. What this paper adds: What is already known on the subject: Stuttering treatment via TP has been proven to be feasible and successful across a variety of treatment programs (e.g., Lidcombe, Camperdown). However, the viability of assessing stuttering via videoconferencing has never been explored in children. What this paper adds to existing knowledge: Preliminary support for the assessment of overt stuttering in CWS aged 6–15 years via video conferencing. The results justify larger scale studies of this service delivery method. What are the potential or actual clinical implications of this work?: The TP system and equipment chosen in this study has provided a basis for the delivery of TP overt stuttering assessment in a clinical setting, thus addressing the barriers to access that are present for CWS aged 6–15 years.